Particulate nutrient data from 2016 mesocosm experiment manipulating Si:N and copepod grazing on Baltic Sea plankton community - Kriste Makareviciute-Fichtner (PANGAEA, 2021)
Changes in silicon to nitrogen (Si:N) ratios are known to affect phytoplankton community composition, as silicon is an essential nutrient for diatoms but not for most other phytoplankton. Less is known if and how this ratio affects biochemical composition and stoichiometry of seston. This is of importance, as changes in seston chemistry can have implications on the quality of food available for zooplankton. We applied a range of Si:N ratios and two levels of copepod grazing on a natural Baltic sea plankton community pre-filtered with 125um mesh size filter. Si:N ratios were achieved by adding silicate (at target concentrations of 10, 16, 22, 28 and 34 μmol L-1) and nitrate solutions (at target nitrogen concentration of 40 μmol L-1) to the experimental units at the start of the experiment. Copepod grazing was manipulated by adding 30 individuals of adult Eurytemora affinis copepods per liter to high copepod treatments once phytoplankton bloom has established (day 6 of the experiment). The mesocosm experiment was carried out in summer 2016 and lasted 20 days. The response of particulate carbon, nitrogen, phosphorus was followed by sampling three times per week and fatty acid samples were taken at the end of the experiment. Our data reveals that increasing Si:N ratios result in an increase of particulate carbon, phosphorus, nitrogen and total fatty acid concentrations. Carbon to nitrogen (C:N) and carbon to phosphorus (C:P) ratios increased with increasing Si:N ratios as well as the concentrations of individual essential fatty acids such as DHA and EPA per seston carbon. Enhanced copepod grazing affected C:N, C:P and DHA and ALA concentrations negatively. Consequently, this data illustrates the importance of bottom up effects such as changes in Si:N ratio and top-down controls like copepod grazing in shaping particulate nutrient and fatty acid composition of marine seston.